An Email to Readable Vietnamese Text Conversion Algorithm for Use in TTS Application - Tran, D.C. (Institute of Electrical and Electronics Engineers Inc., 2020)
In recent years, the growth of corporates' businesses worldwide has driven the setups of call centers for supporting global customers 24/7 across the globe. However, many of the call centers are operated by human manually. Thus, there is need for developing automatic call center which is powered by artificial intelligence (AI), hence reducing operational costs through automation of calls, answering calls, conducting surveys, and receiving customer feedbacks. In this context, recently developed engines such as FPT.AI serves well local customers since it supports well the national language. However, it's text-to-speech (TTS), an essential part of the complete engine, is currently having difficulties in reading customer emails. Therefore, this work presents an email to readable Vietnamese text conversion algorithm for use in TTS application. The average processing time tested on 60 emails is 1.7 milliseconds (ms). By manually validating the dataset, it is found that the algorithm achieves accuracy of up to 86.67. Â© 2020 IEEE.